أثر ألعاب التواصل الاجتماعي على قيم المراهقين - صالح، صالح عبد العزيز (Kulliyyah of Education, International Islamic University Malaysia, 2022)
This research aims to investigate the nature of the relationship between social communication games (PUBG) and (Fortnite) and the Cognitive values that are aggressive and motivating to learn and distract attention among the Mozambit teenage students in the high schools of Ghardaia in the state of Algeria, and to achieve the goals of the study, the researcher used mixed methods the qualitative and quantitative approaches, he prepared an interview and three measures: aggressive and Motivational behavior for learning and distraction. A sample of (430) students was distributed during the second semester of (2019/2020). The study revealed the following results: Both the (PUBG) and (Fortnite) electronic games reflect the following Cognitive values: (44%) of the students possess an average level of aggression. (83%) of students have an average motivation to learn. (48%) of students have an average distraction. There are also differences in aggressive behaviour statistically significant among students and in favor of the age group for (19) years. The study recommended that students should be cared for as the nation’s hope and future, by preparing integrated programs to invest in their free time, in a way that secures them against cyber violence. In addition, encourage developers to develop electronic games in line with Islamic culture .